Potential and Contribution of Hotel Tax and Restaurant Tax to PAD : City of Surabaya - Suparman Suparman; Aris Sunarya; Sarwani Sarwani; Sri Kamariyah (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
This study explores the potential and contribution of hotel and restaurant taxes to Regional Original Revenue (PAD) in Surabaya, Indonesia. Using a qualitative descriptive approach, data were obtained from both primary and secondary sources. Primary data came from the Regional Government of Surabaya and the Regional Revenue Agency, while secondary data included academic literature, statistical reports, and regulatory documents. Data analysis employed McNabb’s (2002) framework, which consists of grouping information by relevant constructs, identifying interpretive bases, generating generalizations, testing alternative interpretations, and refining theory from case evidence.The findings reveal that the hotel and restaurant sectors in Surabaya possess considerable growth potential, supported by increasing investment, a steady rise in tourist arrivals, and the growing public interest in the property and culinary industries. Hotel taxes have contributed an average of 4.96% of PAD annually, while restaurant taxes contributed 8.06%, reflecting their critical role in strengthening local fiscal capacity. Revenue performance has been further enhanced by the implementation of a self-assessment tax system, improvements in taxpayer compliance, and supportive local economic infrastructure. Despite these positive contributions, several challenges remain. These include unregistered lodging facilities, limited enforcement mechanisms, and a shift in consumer demand toward smaller-scale hospitality businesses, which can reduce taxable capacity. Addressing these challenges requires optimizing the hospitality tax base, expanding tourism promotion, strengthening compliance monitoring, and advancing digital-based tax management systems to ensure efficiency and transparency. In conclusion, hotel and restaurant taxes play a vital role in ensuring Surabaya’s fiscal independence and financing public welfare initiatives. Strengthening governance and adopting adaptive policies are essential for maximizing their potential contribution to sustainable local development.